Ultrafast-Laser Micro-Structuring of LiNi0.8Mn0.1Co0.1O2 Cathode for High-Rate Capability of Three-Dimensional Li-ion Batteries - Minh Xuan Tran; Smyrek, Peter; Park, Jihun; Pfleging, Wilhelm; Lee, Joong Kee (MDPI, 2022)
Femtosecond ultrafast-laser micro-patterning was employed to prepare a three-dimensional (3D) structure for the tape-casting Ni-rich LiNi0.8Mn0.1Co0.1O2 (NMC811) cathode. The influences of laser structuring on the electrochemical performance of NMC811 were investigated. The 3D-NMC811 cathode retained capacities of 77.8% at 2 C of initial capacity at 0.1 C, which was thrice that of 2D-NMC811 with an initial capacity of 27.8%. Cyclic voltammetry (CV) and impedance spectroscopy demonstrated that the 3D electrode improved the Li+ ion transportation at the electrode-electrolyte interface, resulting in a higher rate capability. The diffusivity coefficient DLi+, calculated by both CV and electrochemical impedance spectroscopy, revealed that 3D-NMC811 delivered faster Li+ ion transportation with higher DLi+ than that of 2D-NMC811. The laser ablation of the active material also led to a lower charge-transfer resistance, which represented lower polarization and improved Li+ ion diffusivity.